Design and validation of the brand personality scale in food industries - Cruz-Tarrillo, Joel; Inaguazo, Jazmin; Rodriguez-Rosales, Clara; Tarrillo-Paredes, José; Paz-Vilchez, Jose E. (Frontiers in Communication, 2025)
In the competitive context in which food industries operate, the brand plays a predominant role in differentiating and establishing an emotional connection with customers. However, despite being an important factor, only some studies analyze brand personality in this context. This research aimed to develop and validate a brand personality scale, a practical tool that brands in the food sector can use to analyze the position of their brands and make correct strategic marketing decisions. An exhaustive literature review was carried out to generate an initial set of items. Based on surveys in person with 510 consumers in three cities in Ecuador, confirmatory and exploratory factor analyses were carried out to extract the relevant factors. The results show a four-dimensional structure: innovative, creative, honest, and rugged. The results obtained support the reliability and validity of the construct, which implies that brands in the food sector can use this scale to analyze the position of their brands and make correct strategic marketing decisions.